Effects of pulsed operations on isothermal reactions in a CSTR. - Escoto, Angela D.
This paper shall look into the possible effects of deliberate unsteady state processing brought about by introducing sinusoidal fluctuations to stable plants. This practice is commonly referred to as PULSED operations. Effects of input disturbances such as sinusoidal variations in feed rate and/or feed composition are reflected on the time average value of the system output. It will be shown that the time average performance from periodic reactor operation is sometimes superior to that obtained from steady state processing.